2022
DOI: 10.5337/2022.208
|View full text |Cite
|
Sign up to set email alerts
|

Data quality deterioration in the Lake Tana Sub-basin, Ethiopia: scoping study to provide streamflow and water withdrawal data

Abstract: The publications in this series record the work and thinking of IWMI researchers, and knowledge that the Institute's scientific management feels is worthy of documenting. This series will ensure that scientific data and other information gathered or prepared as a part of the research work of the Institute are recorded and referenced. Working Papers could include project reports, case studies, conference or workshop proceedings, discussion papers or reports on progress of research, country-specific research rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Worqlul et al [48] used old streamflow data from surrounding catchments to parametrize a hydrologic model in the Robit and Dangishta catchments of the upper Blue Nile basin. Moreover, unreliable streamflow data was observed in the low flow of the Gilgel Abay river after 2006, which jumped from the long-term average by about 200% [32,50,51].…”
Section: Implication Of Streamflow Data Gapsmentioning
confidence: 99%
See 2 more Smart Citations
“…Worqlul et al [48] used old streamflow data from surrounding catchments to parametrize a hydrologic model in the Robit and Dangishta catchments of the upper Blue Nile basin. Moreover, unreliable streamflow data was observed in the low flow of the Gilgel Abay river after 2006, which jumped from the long-term average by about 200% [32,50,51].…”
Section: Implication Of Streamflow Data Gapsmentioning
confidence: 99%
“…The impetus for this review is the increasing number of studies that reported existing problems of streamflow monitoring in Ethiopia and called for action [32][33][34]. We also hypothesize that hydrological services in African counties would greatly benefit from the findings of studies that address priority research questions in streamflow monitoring and, hence, the need to identify them for the region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation